2019
DOI: 10.1002/maco.201911048
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the random transients caused by clustered pitting corrosion for Al–Mg microelectrode

Abstract: The clustered pitting corrosion process has been investigated by electrochemical noise measurement using two nominally identical Al–Mg microelectrodes in aerated 3.5 wt% NaCl solution (pH 3.5). Current transients associated with the metastable pitting were detected and the pits were examined by scanning electron microscopy (SEM) observation. The results show that two types of clustered pits can be characterized by current transients separately. Pit interaction is confirmed by one transient with multiple peaks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[28] EN assessments are commonly performed using two working electrodes (WEs) whose connection is provided through a zero-resistance ammeter (ZRA), which monitors the coupling current of inter-WEs. [29][30][31] Although two similar WEs (equal size and type) setting a symmetrical cell are commonly used to measure the electrochemical current noise (ECN), [32] current research indicates that asymmetric cell configuration using considerably different sizes of two WEs that can be otherwise identical will be preferable in measuring ECN on Al and mild steel alloys. [29,30,33,34] The authors did not find any paper about the efficiency of asymmetrical Mg electrodes (different size, equal type) in the measurement of ECN after exact reviewing of the relevant literature in this subject.…”
Section: Introductionmentioning
confidence: 99%
“…[28] EN assessments are commonly performed using two working electrodes (WEs) whose connection is provided through a zero-resistance ammeter (ZRA), which monitors the coupling current of inter-WEs. [29][30][31] Although two similar WEs (equal size and type) setting a symmetrical cell are commonly used to measure the electrochemical current noise (ECN), [32] current research indicates that asymmetric cell configuration using considerably different sizes of two WEs that can be otherwise identical will be preferable in measuring ECN on Al and mild steel alloys. [29,30,33,34] The authors did not find any paper about the efficiency of asymmetrical Mg electrodes (different size, equal type) in the measurement of ECN after exact reviewing of the relevant literature in this subject.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 For instance, the effects of heterogeneity of Al alloy surfaces on the initiation and growth behavior of pitting corrosion were investigated. 11,[13][14][15][16][17] However, according to Lu et al, the opencircuit pit growth of Al alloys is controlled by cathodic reactions and is relevant to corrosion in actual environments, but an artifact will be produced under an applied potential because a potentiostat will provide as much current as can be consumed. 18 They investigated the metastable pitting of Al thin films at open-circuit, and they demonstrated that the open-circuit pits grow more slowly than pits that were grown potentiostatically at the same potential.…”
mentioning
confidence: 99%
“…18,19 However, in contrast to round pits on stainless steels, 20 the metastable pits on Al alloys are of diverse morphologies, such as clustered pits, filiform-type pits, and crystallographic pits. 16,21 The sequential changes in the pit morphology, from initiation to growth and repassivation, and their relation to OCP remain unclear. In this study, a system that combines a micro-electrochemical technique and optical microscopy was adopted, and in situ real-time observations of metastable pitting and OCP monitoring were conducted in 0.1 M NaCl.…”
mentioning
confidence: 99%